Hubungan Penggunaan Media Visual dengan Prestasi Belajar Siswa Mata Pelajaran PAI - Arman Paramansyah; Nur Azizah; Ernawati Ernawati; Riyanto Riyanto (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2021)
The problem to be answered in this paper is the relationship between the use of visual media and the learning achievement of PAI students at SDN Kedung Waringin 02, Bojong Gede Bogor. The writing uses descriptive quantitative research in the correlation approach (correlational research). Correlation research is research conducted to find out whether there is a relationship and if there is, how close the relationship is and whether or not the relationship is meaningful. The main purpose of this research is to find out how much the implementation of the relationship between the use of visual media and student learning outcomes in PAI subjects. The writing concludes that the rxy is 0.291, the figure is in the range of 0.20 – 0.39. This means that the X variable to the Y variable has a low or weak positive correlation. The coefficient of determination (determination) is 8.46%. This shows that the relationship between the use of learning media and student learning outcomes with KD 8.46%, while the remaining KD of 91.54% student learning outcomes are influenced by other factors such as the home or family environment and the community environment or living situation, and other factors not analyzed. tcount < ttable, then Ho is accepted and Ha is rejected, then Ho is accepted and Ha is rejected because tcount (840) > ttable (1.970). From the calculation results above, it can be seen that ttcount is smaller than ttable, meaning Ho is accepted and Ha is rejected, so the hypothesis that the author proposes cannot be accepted. Based on these findings, it is recommended that teachers not only improve teacher performance, the process of implementing teaching in the classroom also plays an important role for the success of student learning. Teachers are required to present material that makes students active. teachers can master, understand and try to be skilled and creative in conducting questions and answers with students, to relevant agencies as education providers there are conducive facilities and infrastructure so that the teaching and learning process will take place well and effectively.